Comparison of file sanitization techniques in usb based on average file entropy valves - Onn, Nur Amanina (2018)
Nowadays, the technology has become so advanced that many electronic gadgets are in every household today. The fast growth of technology today gives the ability for digital devices like smartphones and laptops to have a huge size of storage which is letting people to keep many of their infonnation like contact lists, photos, videos and even personal infonnation. When these infonnation are not useful anymore, users will delete them. However, the growth of technology also letting people to recover back data that has been deleted. In this case, users do not realise that their deleted data can be recovered and then used by unauthorized user. The data deleted is invisible but not gone. This is where file sanitization plays it role. File sanitization is the process of deleting the memory of the content and over write it with a different characters. In this research, the methods chosen to sanitize file are Write Zero, Write Zero Randomly and Write Zero Alternately. All of the techniques will overwrite data with zero. The best technique is chosen based on the comparison of average entropy value of the files after they have been overwritten. Write Zero is the only technique that is provided by many software like WipeFile and BitKiller. There is no software that provide Write Zero Randomly technique except for sanitizing disk using dd. As for that, Write Zero Randomly and proposed technique, Write Zero Alternately are developed using C programming language in Dev-C++. In this research, sanitization with Write Zero has the lowest average entropy value for text document (TXT), Microsoft Word (DOCX) and image (JPG) with 100% of data in the files undergone this technique have been zero-filled compared to Write Zero Randomly and Write Zero Alternately. Next, Write Zero Alternately is more efficient in tenns of average entropy by 4.64 bpB to its closest competitor which is Write Zero Randomly with 5.02 bpB. This shows that Write Zero is the best sanitization method. These file sanitization techniques are important to keep the confidentiality against unauthorized user.